2002
DOI: 10.1097/00006123-200204000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Extraction of Oxygen and Intracranial Hypertension in Severe, Acute, Pediatric Brain Trauma: Preliminary Novel Management Strategies

Abstract: In severe, acute, non-missile pediatric brain trauma, phasic physiological patterns demonstrated an association between the development of intracranial hypertension and relative cerebral hyperperfusion (decreased global CEO(2)), especially after postinjury Day 1. Unfavorable clinical outcomes were significantly related to more pronounced intracranial hypertension and more profound concomitant decreases in CEO(2), indicating hyperoxic uncoupling between global cerebral consumption of oxygen and cerebral blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 16 publications
0
42
0
2
Order By: Relevance
“…In our experience, ICP, CPP, and CEO 2 monitoring and management have lasted approximately 7-10 days for both adults 2,4,9,11 and children 12 17 first demonstrated that, immediately following intravenous bolus injections of barbiturates for the treatment of elevated ICP refractory to ongoing optimized mannitol and optimized hyperventilation, blood pressure may fall, along with SjO 2 decreases (CEO 2 increases) in some patients. Therefore, caution should be exercised whenever intravenous barbiturate boluses are administered for ICP control, and the use of vasopressor drugs should be immediately instituted if necessary.…”
Section: Optimized Hyperventilation Optimized Hyperventilation Optimimentioning
confidence: 84%
See 4 more Smart Citations
“…In our experience, ICP, CPP, and CEO 2 monitoring and management have lasted approximately 7-10 days for both adults 2,4,9,11 and children 12 17 first demonstrated that, immediately following intravenous bolus injections of barbiturates for the treatment of elevated ICP refractory to ongoing optimized mannitol and optimized hyperventilation, blood pressure may fall, along with SjO 2 decreases (CEO 2 increases) in some patients. Therefore, caution should be exercised whenever intravenous barbiturate boluses are administered for ICP control, and the use of vasopressor drugs should be immediately instituted if necessary.…”
Section: Optimized Hyperventilation Optimized Hyperventilation Optimimentioning
confidence: 84%
“…As a humanitarian alternative to those 1996 "guidelines" 1 , the present practical and comprehensive guidelines address not only treatment of intracranial pressure (ICP) and CPP but also cerebral ex-traction of oxygen (CEO 2 ) 2,4,[7][8][9][10][11][12] . The latter represents the ratio of global cerebral consumption of oxygen (CCO 2 ) to cerebral blood flow (CBF) 8 , and thus provides accurate bedside information regarding coupling or uncoupling between CBF and CCO 2 .…”
Section: Practical and Comprehensive Guidelines For Bedside Cerebral mentioning
confidence: 99%
See 3 more Smart Citations